Image acquisition and image processing enhancement of 3D X-ray CT images of electronic devices - Ong, Maverique Wen-Kai (Nanyang Technological University, 2024)
In the realm of hardware assurance, 3D X-ray Computed Tomography (CT) has been beneficial in enabling users to view the features within an electronic device without having to break it open. However, with devices continuously shrinking in size and increasing in complexity, such a technique may encounter difficulties in producing high-resolution images with low noise, which can cause submicron features to be distorted by noise and consequently not be properly identified. Therefore, this makes analysis of very-large-scale integration (VLSI) digital integrated circuits, to understand their functionality or to detect any malicious modifications, extremely difficult.